APOE isoforms in focal epilepsies: an association study in a Portuguese population - Martins da Silva, A. (2014)
Purpose: Apolipoprotein E (ApoE) is the main lipoprotein secreted in brain. It has a critical immuno-modulatory function, influences neurotransmission and is involved in repairing damaged neurons. ApoE e4 allele is an isoform of ApoE with altered protein function previously associated with refractoriness and early onset epilepsy. Our purpose was to investigate if apoE isoforms are risk factors for partial epilepsy and to correlate genotypes with anti-epileptic drug response. Methods: A cohort of 230 epileptic patients with partial epilepsies from the outpatient clinic at HSA-CHP [109F, 121M; mean age = 44 13 years, age of onset = 15 13 years; 168 patients with Drug Refractory Epilepsy (DRE)] was compared with a cohort of 301 healthy individuals (HI) in a case control study. ApoE isoforms were genotype by RFLP-PCR methodology. Results: ApoE e4 allele frequency was higher in epileptic group when compared with HI (10.6% vs. 7.6%, p = n.s., OR = 1.44, 95% CI: 0.945–2.20). Anti-epileptic Drug response was not influenced by apoE isoforms. Conclusion: Our results suggest that ApoE e4 may be a risk factor for partial epilepsy development. ApoE e4 is associated with CNS network instability, with lower protection against oxidative and inflammatory cascade. These could influence neuronal growth and recovery leading to a chronic vicious cycle of damage and neuronal loss contributing to seizures development. These observations should be confirmed in a larger cohort.